2023
DOI: 10.1186/s12906-023-03916-x
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral and ROS scavenging potential of Carica papaya Linn and Psidium guajava leaves extract against HIV-1 infection

Abstract: Antiretroviral therapy is the only treatment option for HIV-infected patients; however, it has certain drawbacks in terms of developing multiple toxic side effects. Thus, there is a continuous need to explore safe and efficacious anti-retroviral agents. Carica papaya Linn and Psidium guajava are known for their various biological activities. In this study, we characterized the bioactive fractions of methanolic leaves extract from both plants using the High-resolution electrospray ionization mass spectrometry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The inhibition of HIV-1 Protease is a key focus in the development of HIV treatments, and recent studies have shown that phytomolecule may be effective inhibitors of this enzyme [ [31] , [32] , [33] ]. In these study, the in silico molecular docking simulations analysis revealed diosgenin as a lead phytomolecule that established two hydrogen bonds with Asp29 and Asp30 and many hydrophobic interactions with Gly48, Gly49, Ile50, Gly52, Phe53, Pro79, Thr80, Pro81 and Pi-alkyl contact with Ala28, Val32, Ile47, Ile54, Ile84 residues available in the active site binding pocket of HIV-1 Protease ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of HIV-1 Protease is a key focus in the development of HIV treatments, and recent studies have shown that phytomolecule may be effective inhibitors of this enzyme [ [31] , [32] , [33] ]. In these study, the in silico molecular docking simulations analysis revealed diosgenin as a lead phytomolecule that established two hydrogen bonds with Asp29 and Asp30 and many hydrophobic interactions with Gly48, Gly49, Ile50, Gly52, Phe53, Pro79, Thr80, Pro81 and Pi-alkyl contact with Ala28, Val32, Ile47, Ile54, Ile84 residues available in the active site binding pocket of HIV-1 Protease ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A reference compound, standard diosgenin (Sigma Aldrich, MO, USA) were tested in each set of experiments for the comparative study. The methodology for these experiments was adopted from our earlier research work on this topic, with minor changes in the experimental setup [ [30] , [31] , [32] , [33] , [34] , [35] ].…”
Section: Methodsmentioning
confidence: 99%
“…Metabolic compounds are precursors to the synthesis of secondary metabolites, which are essential for plant development and stress response [ 25 ]. Jadaun et al [ 49 ] observed a variety of metabolic compounds in Indian PL, including steroids, alkaloids (peptides and amino acids), glycosides, lipids, phenolic compounds (aromatic phenol, quinone, and flavonoids), terpenes, aliphatic compounds (fatty acids, alcohol, saturated, and unsaturated alkenes), and other bioactive compounds. Moreover, Indian papaya seed contained 14 metabolic compounds, including oleic acid, stearic acid, methyl ester, dibenzoyl-L-tartaric acid, palmitic acid, and phenol, 2-methoxy-5-prophenyl-(E) [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The silver nanocomposition prepared from the leaf extract of C. roseus, developed by the Department of Microbiology, Dyanopasak Shikshan Mandal, Parbhani, was evaluated for its anti-HIV-1 activity at the Indian Council of Medical Research -National AIDS Research Institute, Pune (ICMR-NARI), following the standard protocol outlined by Gaikwad et al (2023). The biological activity of AgNP-CR was assessed using high-throughput cell-based mechanistic studies, as previously described (Jadaun et al, 2022;Jadaun et al, 2023).…”
Section: Antiviral Assessment Of Agnp-crmentioning
confidence: 99%